Sex-Specific Life History Affected by Stocking in Juvenile Brown Trout - Palejowski, Hugo; Bylemans, Jonas; Ammann, Victor; Marques da Cunha, Lucas; Nusbaumer, David; Castro, Isabelle; Uppal, Anshu; Mobley, Kenyon B.; Knörr, Susanne; Wedekind, Claus (Frontiers in Ecology and Evolution, 2022)
Salmonids are a socioeconomically and ecologically important group of fish that are often managed by stocking. Little is known about potential sex-specific effects of stocking, but recent studies found that the sexes differ in their stress tolerances already at late embryonic stage, i.e. before hatchery-born larvae are released into the wild and long before morphological gonad formation. It has also been speculated that sex-specific life histories can affect juvenile growth and mortality, and that a resulting sex-biased demography can reduce population growth. Here we test whether juvenile brown trout (Salmo trutta) show sex-specific life histories and whether such sex effects differ in hatchery- and wild-born fish. We modified a genetic sexing protocol to reduce false assignment rates and used it to study the timing of sex differentiation in a laboratory setting, and in a large-scale field experiment to study growth and mortality of hatchery- and wild-born fish in different environments. We found no sex-specific mortality in any of the environments we studied. However, females started sex differentiation earlier than males, and while growth rates were similar in the laboratory, they differed significantly in the field depending on location and origin of fish. Overall, hatchery-born males grew larger than hatchery-born females while wild-born fish showed the reverse pattern. Whether males or females grew larger was location-specific. We conclude that juvenile brown trout show sex-specific growth that is affected by stocking and by other environmental factors that remain to be identified.